Exploring the long-term exchange rate volatility in Turkey: Evidence from a garch-midas model - POLAT, UMURCAN (My University, 2022)
This study aims to understand the dynamics of long-term exchange rate volatility in Turkey grounded on a mixed data sampling model and see how macroeconomic fundamentals stand for the long-term component of volatility under the floating regime period i.e., for the post-2001 episode. More specifically, we employ the GARCH-MIDAS model to link series sampled at different frequencies and obtain short- and long-term components of volatility. We estimate the model by replacing the realized volatility with exogenous regressors. We control the Beta weights and estimate the model under different samples and for various variables for robustness. Also, we employ the ARDL model to see the longrun relation when series are sampled at the same frequency. We find that the long-term volatility features a high degree of persistence pattern, and the volatility patterns partially occur to absorb shocks to macroeconomic variables.

Bu çalışma, karma veri örnekleme modelini kullanarak Türkiye’deki uzun dönemli döviz kuru oynaklığının dinamiklerini anlamayı ve 2001 sonrası serbest kur rejimi döneminde makroekonomik temel değişkenlerin oynaklığın uzun vadeli bileşenini nasıl temsil ettiğini görmeyi amaçlamaktadır. Daha spesifik olarak, farklı frekanslarda örneklenen serileri ilişkilendirmek ve kısa ve uzun vadeli oynaklık bileşenlerini elde etmek için GARCH-MIDAS modelini kullanmaktayız. Gerçekleşen oynaklığı dışsal açıklayıcı değişkenlerle değiştirerek model tahminini gerçekleştirmekteyiz. Beta ağırlıklarını kontrol edip ve modeli farklı örnekler altında ve çeşitli değişkenler için tahmin etmekteyiz. Ayrıca, seriler aynı frekansta örneklendiğinde uzun dönemli ilişkiyi görmek için ARDL modelini kullanmaktayız. Uzun vadeli oynaklığın yüksek derecede kalıcılık özelliğine sahip olduğunu ve oynaklık modellerinin kısmen makroekonomik değişkenlere yönelik şokları absorbe etmek için ortaya çıktığını gözlemlemekteyiz.
Türkiye’deki uzun dönemli döviz kuru volatilitesinin araştırılması: Bir garch-midas modeli üzerinden kanıt
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); GARCH-MİDAS Modeli; Döviz Kurları; Volatilite; Türkiye; GARCH-MIDAS Model; Exchange Rates; Volatility; Turkey